Peningkatan Kualitas Data Kependudukan melalui Program Kemitraan Masyarakat Tertib Administrasi Kependudukan - Nafsiatun (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2019)
Punggur Kecil Village, Sungai Kakap District, Kubu Raya Regency, West Kalimantan Province is one of the developing villages. Therefore, it requires structuring in the field of population administration, especially administration of birth, death and marriage. The PKM Team of the Faculty of Law, Tanjungpura University in collaboration with the Punggur Kecil Village Government conducted the PKM Orderly Population Administration activities. PKM activities include socialization, counseling and education. Improvements to population administration include birth, death and marriage. This activity was able to improve order administration in Punggur Kecil Village. Increasing orderliness in population administration has had an effect on the mapping of the population of Punggur Kecil Village so that it can carry out a strategy to empower its population to improve their welfare. The results of monitoring and evaluation of activities carried out before and after the activity showed 77% increase in understanding of the community of Punggur Kecil Village towards orderly population administration. Before PKM activities 97% of the people said they had never received counseling on population administration. After this PKM activity, 77% of the Punggur Kecil Village community were satisfied. As many as 23% of the community were dissatisfied because the PKM implementation time was not long enough. This is evidenced by 100% of the community asking for the PKM Team of the Faculty of Law of Tanjungpura University to do another PKM in Punggur Kecil Village with a different theme so that the Village of Punggur Kecil is further advanced.